2002
DOI: 10.1172/jci0215506
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of phosphodiesterase 4D in mice shortens α2-adrenoceptor–mediated anesthesia, a behavioral correlate of emesis

Abstract: A combination of pharmacological and genetic approaches was used to determine the role of type 4 cAMP-specific cyclic nucleotide phosphodiesterase 4 (PDE4) in reversing alpha(2)-adrenoceptor-mediated anesthesia, a behavioral correlate of emesis in non-vomiting species. Among the family-specific PDE inhibitors, PDE4 inhibitors reduced the duration of xylazine/ketamine-induced anesthesia in mice, with no effect on pentobarbital-induced anesthesia. The rank order of the PDE4 inhibitors tested was 6-(4-pyridylmeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
138
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(153 citation statements)
references
References 33 publications
4
138
1
2
Order By: Relevance
“…This mechanism may regulate the analgesic efficacy of opioids without direct recruitment of ␤-arrestin2 by MORs. Our findings support early data in rodents (38), as well as more recent findings including studies on PDE4 KO mice (39), and human clinical trials indicating that centrally active PDE4 …”
Section: Pre-and Postsynaptic Inhibition Of Lc Neurons By Morphinesupporting
confidence: 92%
“…This mechanism may regulate the analgesic efficacy of opioids without direct recruitment of ␤-arrestin2 by MORs. Our findings support early data in rodents (38), as well as more recent findings including studies on PDE4 KO mice (39), and human clinical trials indicating that centrally active PDE4 …”
Section: Pre-and Postsynaptic Inhibition Of Lc Neurons By Morphinesupporting
confidence: 92%
“…In addition, reversal of ␣2-adrenergic receptor-induced anesthesia has been used as a surrogate test for emesis in mouse and rat, which do not exhibit the emetic reflex. PDE4D but not PDE4B ablation impacts this surrogate response, again suggesting that the emetic response is the result of PDE4D inhibition (44). Thus, drugs that preferentially inhibit PDE4B over PDE4D should retain many of the beneficial anti-inflammatory effects with fewer unwanted CNS effects.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial of rolipram reported acceptable tolerance levels at clinically relevant doses (Fleischhacker, Hinterhuber et al 1992). In clinical and preclinical trials, the main human PDE4 inhibitor side effect, thought to be due to PDE4D activity (Robichaud, Savoie et al 2002;Robichaud, Stamatiou et al 2002;Conti, Richter et al 2003), is emesis at clinical doses while rats are more susceptible to toxic effects like arteriopathy. One explanation for this effect is the reduced PDE4 enzyme activity in humans relative to monkeys and rats (Bian, Zhang et al 2004).…”
Section: Camp Therapymentioning
confidence: 99%